The effect on the usage of mechanical ventilation in heritage building in Johor Bahru / Muhammad Akmal Sugeng Triwahyono - Sugeng Triwahyono, Muhammad Akmal (2021)
This research was carried out with the main purpose of finding out the conditional usage of mechanical ventilation system in repurposed heritage office buildings. The problem statement of the research point towards the usage hours of the mechanical ventilation system along with the temperature set and the capability for the system to adapt into the heritage building as a retrofitted system in order to provide comfort to the occupants. With those two (2) main points set as the objective of the research, two (2) case studies have been selected in Johor Bahru, Johor area to be conducted a survey process consisting a set of questionnaires that require the respondents to give their responses and feedbacks regarding the mechanical ventilation system in their respective repurposed heritage office buildings. There is a total of five (5) main chapters included in this research, in which the chapter one (1) is the Introduction along with the aim, objectives and problems, method and significance of the research, chapter two (2) on the Literature Review regarding on retrofitted mechanical ventilation system in repurposed heritage office buildings in Malaysia, chapter three (3) for the Research Methodology presenting the approach of the research, research design, sampling, data collection, elaboration on selected case studies, and method for data analysis, chapter four (4) of Results and Discussions of the analysis for the data that were obtained from the survey process with the respondents based on their respective buildings and background factors, and lastly chapter five (5) Conclusions and Recommendations on the data analysis that had been carried out thoroughly along with recommendations and suggestions made for both the research itself and for future research regarding on the scope of this study.